Hyperlactatemia Post-CABG: Case Studies in Three Patients - Wardhana, Ardyan; Kurniawaty, Juni (Majalah Anestesia & Critical Care, 2025)
Introduction: Hyperlactatemia after CABG may signal intra- or postoperative complications by reflecting a mismatch between tissue oxygen supply and metabolic demand, with potential for organ dysfunction and worse outcomes. This case report examined contributing factors—including metabolic acidosis, postoperative metabolic stress, and inotropic agents—to guide targeted interventions and improve clinical results. Case Description: Three patients underwent CABG, with the first and second remaining hemodynamically stable in the ICU on dobutamine and nitroglycerin, whereas the third required norepinephrine, epinephrine, and temporary pacing for instability. None exceeded 4 mmol/L during CPB or immediately after separation, yet all showed immediate-onset hyperlactatemia (IHL)—a phenomenon reported in 17% of cases, especially with longer CPB/cross-clamp times. All subsequently developed late-onset hyperlactatemia (LHL) at 4–12 hours: first and third patient had hyperglycemia, whereas the second reached the highest 12-hour lactate peak without hyperglycemia. LHL likely reflected type-B lactate from postoperative inflammatory/metabolic stress and insulin resistance, typically normalizing within 12–24 hours without a marked drop in base excess. Third patient’s sharp4-hour surge was plausibly epinephrine-related—more consistent with preserved metabolic reserve than with adverse prognosis. Conclusion: In post-CABG patients, hyperlactatemia may arise from non-hypoxic, multifactorial mechanisms (inflammation, metabolic stress, and inotropes) and thus warrants context-aware interpretation and targeted management rather than reflexive attribution to tissue hypoxia.